2019
DOI: 10.1261/rna.071662.119
|View full text |Cite
|
Sign up to set email alerts
|

Structure folding of RNA kissing complexes in salt solutions: predicting 3D structure, stability, and folding pathway

Abstract: RNA kissing complexes are essential for genomic RNA dimerization and regulation of gene expression, and their structures and stability are critical to their biological functions. In this work, we used our previously developed coarse-grained model with an implicit structure-based electrostatic potential to predict three-dimensional (3D) structures and stability of RNA kissing complexes in salt solutions. For extensive RNA kissing complexes, our model shows great reliability in predicting 3D structures from thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 131 publications
(256 reference statements)
0
36
0
Order By: Relevance
“…To predict the 3D structures and stability of RNAs in various ion solutions, we have developed a new CG model with involving the effects of ions (Shi et al, 2014a(Shi et al, , 2015(Shi et al, , 2018Jin et al, 2018Jin et al, , 2019. In the model, each nucleotide is represented by three beads, which represent the three atom groups: phosphate group (P), sugar ring (C), and base (N), respectively.…”
Section: The Cg Structure Model and Force Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…To predict the 3D structures and stability of RNAs in various ion solutions, we have developed a new CG model with involving the effects of ions (Shi et al, 2014a(Shi et al, , 2015(Shi et al, , 2018Jin et al, 2018Jin et al, , 2019. In the model, each nucleotide is represented by three beads, which represent the three atom groups: phosphate group (P), sugar ring (C), and base (N), respectively.…”
Section: The Cg Structure Model and Force Fieldmentioning
confidence: 99%
“…The last term U el in Equation ( 1) is an electrostatic potential corresponding to electrostatic interactions between phosphate groups (a charge of -e for each P bead at its center), which are ignored by most existing predictive models for RNA 3D structures (Hajdin et al, 2010;Rose et al, 2011;Shi et al, 2014b;Schlick and Pyle, 2017). The U el is taken into account through the combination of the Debye-Hückel approximation, the concept of counterion condensation (CC) (Manning, 1978), and the tightly bound ion (TBI) model (Tan and Chen, 2007, and the potential can well-capture the contribution of monovalent/divalent ions to RNA 3D structures (Shi et al, 2015;Jin et al, 2019).…”
Section: The Cg Structure Model and Force Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Fyta et al has developed a four-bead CG model for double-stranded RNA which uses density functional theory to determine the parameters in energy functions and can reproduce the structural and mechanical properties (Cruz-León et al, 2018). Tan et al managed to predict the 3D structures and stability of RNA kissing complexes in monovalent/divalent ion solutions by using a 3-bead CG model (Jin et al, 2019). Even for the large ribosome system, a 1-bead CG model for RNAs and proteins has been applied to study its dynamics (Trylska et al, 2005).…”
Section: Modelsmentioning
confidence: 99%
“…For example, thermodynamic and single-molecule measurements have both shown that an increase in salt concentration would apparently enhance the stability of secondary segments, and a logarithm salt-dependence of the folding free energy/entropy has been empirically derived at relatively high salt concentration (e.g., between ∼0.1-1 M) (SantaLucia 1998;SantaLucia and Hicks 2004). In parallel, the influence of metal ions on the tertiary structure of RNA has been explored extensively (Woodson 2005;Draper et al 2005;Koculi et al 2007;Draper 2008;Tan and Chen 2011;Kim and Shapiro 2013;Li 2013;Wang et al 2015;Wang and Xiao 2016;Shi et al 2018;Xi et al 2018;Hori et al 2019;Jin et al 2019). For example, Li (2013) studied the role of diffuse metal ions in stabilizing a 2-bp kissing complex by single-molecule techniques and found the significant contribution of diffuse cations to the stability of tertiary interaction.…”
Section: Introductionmentioning
confidence: 99%